AN OVERVIEW ON CURRENT REGULATION AND EVALUATION OF BIOCIDAL PRODUCTS - ŞAHİNER, Aslı; YAPAR, Evren ALGIN (Universal Journal of Pharmaceutical Research, 2019)
A biocidal product is a substance or mixture prepared to limit, destroy, neutralize or control the effects of a harmful microorganism, plants and animals. The active substance in a biocidal product can be a natural oil or extract, a chemical substance or a microorganism, virus or fungus. Biocides consist of four main groups: disinfectants, preservatives (wood, paint, etc.), pest control and other type of biocidal products. A biocidal substance can also be added to a product to make the product itself into a biocidal product. These products range from disinfectants, hand sanitizers, preservatives, insect repellents, to rodenticides and insecticides and are used to protect humans, animals, materials and articles by controlling the intended target organism by a chemical or biological action. To make sure the use of biocidal products do not have unacceptable risks for people, animals and the environment, they are regulated to control their marketing, sale and use. In the current study biocidal products have been overviewed in the scope of current European Union regulations, product types and conformity tests. Peer Review History: Received 2 August 2019; Revised 7 September; Accepted 29 October, Available online 15 November 2019 Academic Editor: Dr. Amany Mohamed Alboghdadly , Princess Nourah bint abdulrahman university, Riyadh, amalbgadley@pnu.edu.sa Reviewer(s) detail: Dr. Barkat Ali Khan , Kampala International University , Uganda, barki.gold@gmail.com Dr. Sally A. El-Zahaby , Pharos University in Alexandria, Egypt, sally.elzahaby@yahoo.com